PEMBENTUKAN PERATURAN DAERAH YANG RESPONSIF DALAM MENDUKUNG OTONOMI DAERAH - Suharjono, Muhammad (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2014)
This research aims to generate a responsive regional legislation in support of the implementation of regional autonomy. So that the implementation of regional autonomy does not give birth to new problems that can impede development and economic growth of a region. In this legal research Â used several approach es including; approach primary legislation Law No.32 of 2004 on regional autonomy and Law No.12 of 2011 on the Â establishment of legislation. O ther approach esare being approached on a case, the historical approach, comparative approaches, and conceptual approaches.Keywords: Local regulation, Regional autonomy,authority.